Pharmacological Evaluation of Epigallocatechin Gallate of Green Tea as Wound Healing Agent - Pal, Priyanka; Jain, Ashish (Journal of Neonatal Surgery, 2025)
Green tea is characterized by the high content of polyphenols, which is produced from the tea plant Camellia sinensis. Epigallocatechin gallate (EGCG) is regarded as the most abundant compound in tea leaves with excellent bioactivities, such as antioxidant/free radical scavenging, anti-inflammatory and antimicrobial properties. However, the clinical application of EGCG is restricted by its low bioavailability, since EGCG is unstable under the alkalescent condition of the intestinal track and circulatory system. It was reported that a single injection of EGCG hardly accelerated the healing process of the wound on the back of rats. The potential application of EGCG to skin wound treatment has been investigated, and some positive results in vitro and in vivo have been achieved. The effects of EGCG on wound healing are associated with the application form and the dosage of EGCG, study models and treatment methods.